The need for ICT towards enhancing SMEs' business activities in Shah Alam / Sumaiah Ramli - Ramli, Sumaiah (Faculty of Information Technology and Quantitative Science, 2004)
As ICT is becoming a natural part of our daily lives, its use in industrial sectors is becoming necessity. Whether we realized or not industrial sectors are experiencing an increase in the use of a variety of ICT. The purpose of this research is to determine the level of awareness about the importance of ICT in managing business activities. The focuses were on small medium sized enterprises (SMEs) in Shah Alam which involved various types of industries. This research also focuses on the organization perspective by using a research model based on Technology Acceptance Model (TAM) to identify factors that affect SME's acceptance of ICT. Besides that, this research also highlights the degree of awareness among SME employees regarding the importance of benefits of ICT. Cross tabulation analysis has been performed to investigate whether the I hypothesized attributes, variable and belief structure are correlated with each other. Perhaps this research will give awareness to SMEs about the role of ICT in their organization.